Development of Automated Laser Welding Technology and Equipment for Manufacturing Parts of Marine Engine Heat Exchanger - Shelyagin, V.D.; Lukashenko, A.G.; Khaskin, V.Yu.; Lukashenko, D.A.; Lukashenko, V.A. (Science and Innovation, 2024)
Equipment for laser welding complex, which can apply to machine-building, aerospace, shipbuilding, and automobile industries, has been designed and manufactured on the basis of technique for automated laser welding of flat tubes made of copper-nickel alloys. A method for controlling the integrity of welded flat tubes has been developed. It implies the pressure tests and the search of defective sections by laser interferometry technique in automated mode. A specialized welding head has been designed and manufactured for industrial application of laser welding technique.